Peace Education in the Schools of Nepal - K C, Bishnu Bahadur (Academia Research Journal, 2023)
Political changes took place in the history of Nepal. According to the changed system, there should have been a system of peace education in school education, but it was not. After the change in the state system, peace education should be managed to make the common citizens feel the peace expected. Clear aspects of peace education should be kept in the school curriculum, national education objectives, level objectives, themes, and teaching facilitation. In other forms of education, non-formal education, distance education, teacher training, school seminars and programs like peace education should also be made widespread. In order to make peace in school, society and the country, to awaken the consciousness of peace, to build an ideal and civilized society, the inner peace of every person should be developed. Meditation and yoga aspects should be used in various aspects of school and society. Aspects of peace should be taken as an integral part of daily living and social life. The important aspects of peace should be arranged in school education, the aspects of the Vedas of Eastern philosophy and Tripitaka of Buddhist philosophy should be implemented effectively.